Proceedings. 1991 IEEE International Conference on Robotics and Automation
DOI: 10.1109/robot.1991.131612
|View full text |Cite
|
Sign up to set email alerts
|

The condition for contact grasp stability

Abstract: We distinguish between two types of grasp stability, which we call spatial grasp stability and contact grasp stability. The former is the tendency of the grasped object t o return to an equilibrium location in space; the latter is the tendency of the points of contact to return to an equilibrium position on the object's surface. We show via examples that spatial stability cannot capture certain intuitive concepts of grasp stability and hence that any full understanding of grasp stability must include contact s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 11 publications
0
40
0
Order By: Relevance
“…There is a wide disparity in the terminology used in the grasping literature regarding equilibrium, stability, force closure and form closure terms [2][3][4][5][6][7]. We adopt the terminology used in [4] and summarize in the following the corresponding definitions.…”
Section: Background and Terminologymentioning
confidence: 99%
See 1 more Smart Citation
“…There is a wide disparity in the terminology used in the grasping literature regarding equilibrium, stability, force closure and form closure terms [2][3][4][5][6][7]. We adopt the terminology used in [4] and summarize in the following the corresponding definitions.…”
Section: Background and Terminologymentioning
confidence: 99%
“…They are reflected by properties such as form-closure, force-closure and more generally by the ''contact stability'' [2][3][4][5][6][7].…”
Section: Background and Terminologymentioning
confidence: 99%
“…The fact that studies have shown that slightly concave curvature may be better suited [15] is left as a possible extension to the work. For this task a combination of the Canny edge detector and the k-angular bending algorithm [16] was used.…”
Section: A Finding Good Regions To Graspmentioning
confidence: 99%
“…A concave surface is a better place to put a finger for grasping purposes than a convex one [12]. This feature takes into account the curvature of the three grasp zones.…”
Section: Contact Curvaturementioning
confidence: 99%